From Competency to Itqan: Integrating Prophetic Spiritual Excellence into the Learning Outcomes of the Merdeka Curriculum - Faqih Abdul Aziz; Rohmat Robi' Rozaqiy; Albert Taqy Asy Syakur; Akbar Yusgiantara; Ahmad Yusam Thobroni (Jurnal Pendidikan Islam, 2026)
The integration of Outcome-Based Education (OBE) within Indonesia’s Merdeka Curriculum encounters philosophical friction, as mechanistic competency standards frequently marginalize spiritual values. This study aims to reconstruct OBE’s philosophical foundation by synthesizing Prophetic Traditions into a holistic instructional design model. Employing a qualitative library method alongside a hermeneutic synthesis approach, this research systematically analyzes five canonical Hadiths to establish a robust "Prophetic OBE Framework." The findings articulate three fundamental reconstructions. First, concerning learning objectives, the study proposes a hierarchical taxonomy rooted in the Hadith of Jibril (Islam-Iman-Ihsan) and a strict prerequisite logic, termed Prophetic Scaffolding, derived from the Hadith of Mu'adz, prioritizing Adab (etiquette) prior to cognitive mastery. Second, within the learning process, the concepts of "Spiritual Agility" (Hadith of Hanzalah) and "Ecological Behaviorism" (Hadith of the Murderer of 100) are introduced to humanize the educational ecosystem, ultimately mitigating toxic productivity. Third, regarding assessment, the paradigm firmly shifts from minimal competency towards Itqan (Spiritual Excellence). By analyzing the Hadith of the Cave, this research formulates the "Cave Assessment Model," measuring student success through an "Authentic Portfolio" of real-world problem-solving rather than merely standardized testing. Ultimately, this study advocates comprehensive national assessment reforms shaping exceptional professional graduates.